Study on Surrounding Rock Deformation Laws of an Argillaceous Soft Rock Roadway Based on the Creep Damage Model - Chen, Fengbin; Su, Rui; Yang, Liuhua; Yang, Xiaolin; Jiao, Huazhe; Zhu, Changxing (Frontiers in Earth Science, 2022)
The indexes of argillaceous soft rocks in Western China, such as rock strength and softening coefficient, are much smaller than those of soft rocks commonly seen in other areas. Such argillaceous soft rocks are susceptible to a more serious creep phenomenon if encountering water. Accordingly, the study theoretically constructed a constitutive creep model considering the weakening coefficient and damage of surrounding rocks. Next, the viability of this model was verified by combining numerical simulation and field monitoring. Accordingly, this study conducted a comparative analysis on the creep range and cross-sectional deformation of argillaceous surrounding rocks of a roadway in a titled stratum under dry and damp states. Results showed that the Cvisc model considering the weakening coefficient of surrounding rocks was applicable to the decay creep and uniform creep stage, and that considering the damage of surrounding rocks was applicable to the accelerated creep stage. During the creep process, the argillaceous surrounding rocks were prone to viscoelastic deformation. The damp state had an obvious time effect on the damage of surrounding rocks. Specifically, the creep range was expanded under a damp state at 18 d compared with that under a dry state, and the change in the left and upper displacements was especially significant. The roadway cross-section changed asymmetrically under both dry and damp states, where it was changed into an approximate deflected rhombic shape under the dry state and into an approximate deflected trapezoidal shape under the damp state. Additionally, the roadway cross-sectional change under the humid state was evidently greater than that under the dry state.